Dopamine Receptor D3 rs6280 is Associated with Aberrant Decision‐Making in Parkinson's Disease. Issue 4 (19th July 2018) - Rajan, Roopa; Krishnan, Syam; Sarma, Gangadhara; Sarma, Sankara P.; Kishore, Asha
Abstract: Background: The functional Ser9Gly single nucleotide polymorphism (SNP) in the dopamine D3 receptor gene is associated with impulse control disorders (ICD) in Parkinson's disease (PD) in Indian patients. Whether the same SNP modulates impulsivity in PD patients without active ICD is unknown. We aimed to compare decision‐making under uncertainty in PD patients with DRD3 p.S9G (rs6280) variants CT/CC or TT. Methods: We conducted a cross‐sectional study including PD patients (n = 78) whose DRD3 p.S9G (rs6280) genotypic status was known (CC, CT, and TT). Decision‐making was assessed using the Iowa Gambling Task (IGT). Results: IGT total ( p = 0.267) or block scores did not differ between the DRD3 rs6280 variant groups. Deck choice analysis revealed that the CT/CC group showed a skewed preference in deck choice ( p = 0.002) due to significantly fewer draws from deck B, compared to all other decks (deck A, p < 0.001; deck C, p = 0.004; deck D, p = 0.002). Conclusions: The functional Ser9Gly DRD3 variant is associated with aberrant decision‐making under uncertainty in PD patients without active ICD. This ability to modulate impulsivity may underlie its association with clinical ICD in PD.